2019
DOI: 10.1186/s40478-019-0812-5
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic localization of C9orf72 regulates post-synaptic glutamate receptor 1 levels

Abstract: A hexanucleotide repeat expansion in a noncoding region of C9orf72 is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Reduction of select or total C9orf72 transcript and protein levels is observed in postmortem C9-ALS/FTD tissue, and loss of C9orf72 orthologues in zebrafish and C. elegans results in motor deficits. However, how the reduction in C9orf72 in ALS and FTD might contribute to the disease process remains poorly understood. It has been shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 70 publications
8
58
0
Order By: Relevance
“…In this study, we showed that RAB39B is present throughout postnatal life, with the protein being abundant in the neuronal soma of cortical and hippocampus, which have implications for its proposed roles in synaptic maintenance and cognition. These results are consistent with and extend previous reports examining the localization of Rab39b expression and RAB39B protein in mouse brain tissue [3,9]. Notably, we demonstrated that RAB39B is an abundant protein in dopaminergic neurons in the SNpc, the neuronal subtype selectively lost in PD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we showed that RAB39B is present throughout postnatal life, with the protein being abundant in the neuronal soma of cortical and hippocampus, which have implications for its proposed roles in synaptic maintenance and cognition. These results are consistent with and extend previous reports examining the localization of Rab39b expression and RAB39B protein in mouse brain tissue [3,9]. Notably, we demonstrated that RAB39B is an abundant protein in dopaminergic neurons in the SNpc, the neuronal subtype selectively lost in PD.…”
Section: Discussionsupporting
confidence: 93%
“…Further, in-situ hybridization suggested the highest expression was in the hippocampus [3]. Correspondingly, a second study reported localization of RAB39B to mossy fiber synapses of the hippocampus by immunohistochemistry [9]. However, localization of RAB39B to other brain regions was not explored in this study and remains largely unknown.…”
Section: Introductionmentioning
confidence: 61%
“…The C9orf72 protein has been shown to function in a complex with the WDR41 and SMCR proteins as a GEF for Rab8 and Rab39 9,10 . It has also been proposed to play a role in autophagic ux 9,11,12 , endosomal tra cking [13][14][15] and regulating AMPA receptor levels 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In zebra sh, expression of mutant human TARDBP G348C mRNA or FUS R521H resulted in impaired transmission, reduced frequency of miniature endplate currents (mEPCs) and reduced quantal transmission at the NMJ 22,23 . C9orf72 is expressed presynaptically and postsynaptically 16 . The function of C9orf72 at synapses remains an interesting and largely unexplored, yet a full understanding of its synaptic function can extend its contribution to ALS pathogenesis and uncover therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrites are more complex structures formed by multiple branching processes and dendritic spines, which are small protuberance of the plasma membrane where the postsynaptic excitatory apparatus is assembled and are essential for the regulation of postsynaptic receptor levels (17,18). The formation and complexity of these processes is critical to the directional ow of information between neurons in the CNS.…”
mentioning
confidence: 99%